Burden of reduced work productivity among people with chronic knee pain: a systematic review. Issue 9 (28th May 2014) - Agaliotis, Maria; Mackey, Martin G; Jan, Stephen; Fransen, Marlene
Abstract : Objective: The aims of this systematic review were to determine the prevalence of reduced work productivity among people with chronic knee pain as well as specifically categorise determinants of work productivity losses into individual, disease and work-related factors, conduct an evaluation of study methodological quality and present a best-evidence synthesis. Methods: We searched the literature using combinations of key words such as knee pain, knee osteoarthritis, absenteeism (days taken off work) and presenteeism (reduced productivity while at work) for observational studies published in English. Methodological quality appraisal and a best-evidence synthesis were used to pool the study findings. Results: The studies were conducted exclusively in high income countries of North America, Western Europe and Hong Kong. 17 studies were included in the review, 10 measuring absenteeism and six measuring presenteeism. Of the 10 studies reporting absenteeism, seven found a 12-month absenteeism prevalence ranging from 5% to 22%. Only two studies evaluated presenteeism prevalence and reported a range from 66% to 71%. Using best-evidence synthesis: three high quality cohort studies and three cross-sectional studies provided strong evidence that knee pain or knee osteoarthritis was associated with absenteeism; two high quality cross-sectional studies and one cohort study provided limited evidence for an association with presenteeism; one cross-sectional study provided limited evidence for an association among age, high job demands and low coworker support and absenteeism among nurses with knee pain. No studies examined individual or work-related factors associated with presenteeism. Conclusions: A number of high quality studies consistently demonstrated that chronic knee pain or knee osteoarthritis is associated with absenteeism. However, data are lacking regarding presenteeism and individual or work-related risk factors for reduced work productivity among older workers with chronic knee pain. Systematic review registration number: PROSPERO registry number: CRD42013004137.